Teaching Writing and Twenty First Century Skills Using Guided Autonomous Learning Designs - Abdul Ghofur; Kisyani Kisyani; Bambang Yulianto (Budapest International Research and Critics University, 2019)
This article describe how to improve student’s skills in writing French and eight types of the twenty first (21st) century skills Using Guided Autonomous Learning designs. This research is intended to produce and use Guided Autonomous Learning Designs by integrating eight types of 21st century skills in teaching writing French. The designs developed consist of syllabus, learning model, textbook, learning media, and lesson plan. The research data is obtained from students, lecturers, experts, observers, and documents. Data sought are (1) process of developing Guided Autonomous Learning designs by integrating eight types of 21st century skills and their quality based on their validity, practicality, and effectiveness. The data was collected using observation techniques, expert validation, interviews, documents analysis, tests, and questionnaires. The data was analyzed quantitatively and qualitatively using content analytic techniques, conversational analysis, narrative analysis, percentage techniques, average techniques, and correlation techniques. The finding show that Guided Autonomous Learning designs by integrating eight types of 21st century skills are very effective to improve student’s writing in French and eight types of 21st century skills. The average score of the quality (validity, practicality, and effectiveness) of Guided Autonomous Learning designs by integrating eight types of 21st century skills is 3.51. Therefore, this research needs to be developed and implemented in other subjects by integrating other types of 21st century skills.